EVALUATION OF HERBICIDE USE BY FARMERS IN SOUTH AND NORTH OF MUBI LOCAL GOVERNMENT AREAS, ADAMAWA STATE, NIGERIA - JOSEPH, J.; ISHAKU, H.; BUBA, Z.M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
A study to investigate herbicide use and adherence to established protocols for application of herbicides was carried out in Mub-North and Mubi-South Local Government Areas of Adamawa State. A systematic sampling technique was adopted for the study. A total of 200 structured questionnaires were administered to respondents (farmers) to obtain data on aspects related to herbicide use. Data generated was analysed using descriptive statistics. The results obtained revealed that the majority of the farmers use Dragon/Gramazol and 2-4-D categories of herbicides more frequently, while Pentashi and Paraquat were applied infrequently. Also, the results indicated that majority (59%) of the respondents do not adhere to user’s guide provided by the manufacturers of herbicides, though, 162 (81%) agreed that they were aware of adverse effects of herbicides on the environment. Similarly, 172 (86%) of the respondents were aware of effects of herbicides on non-target organisms. Also, 130 (65%) of the respondents do not use proper dress and protective equipment during application of herbicides. The results further revealed that 174 (87%) % of the respondents have used empty containers of herbicides for other purposes. Lastly, the results revealed that 150 (75%) of the respondents have known individuals that have suffered one form of herbicide poisoning. Based on the findings from the study, it is recommended that relevant government agencies should intensify awareness campaign to farmers on the safe use of herbicides and other agrochemicals.